Influence of strategies to determine the significance of the crisis by the managers of small and medium-sized enterprises - Vrchota, Jaroslav; Rehor, Petr (Serbian Journal of Management, 2016)
Small and medium-sized enterprises play an important role in the European economy as a source of entrepreneurial skills, innovation and employment. Strategic management is vital for long-term competitiveness of these organizations, and even more significant when struggling with a crisis. Enterprises with strategic management are able to look into their future and their managers are able to recognize upcoming issues in advance so they are much better prepared for them. Crisis is then perceived as a phenomenon which is more common than rare. It is therefore essential that businesses reflect the aspects and impacts of the crisis in a corporate strategy and managers learn to manage crises effectively. The article deals with a partial research of the management of small and medium-sized enterprises in the Czech Republic. It is focused on defining a strategy by the managers of these organizations and the assessment of the significance of crises. Only about 25% of the companies formulated a strategy for the future direction of the organization. The crises happen in all organizations, varying in degrees and intensity. The importance of crisis is evaluated by the managers by an average rate of 3.4 (where the highest rate was five). The aim of the article is an assessment of the importance of crisis as seen by the managers in strategically managed organizations structured according to sectors of the economy. For primary data collection, the questionnaire method was used.